Anogenital scent-marking signals fertility in a captive female Alaotran gentle lemur - Fontani, Sara; Kaburu, Stefano S. K.; Marliani, Giovanna; Accorsi, Pier Attilio; Vaglio, Stefano (Frontiers in Veterinary Science, 2022)
The Lake Alaotra gentle lemur (Hapalemur alaotrensis) is one of the 25 most endangered primates in the world and shows low success rate in captive breeding programmes. It is therefore vital to further understand its reproductive biology. We studied a captive troop consisting of five individuals hosted at Jersey Zoo during breeding and non-breeding periods over one year. We collected behavioural data (n=318 hours) using all occurrences of some behaviours and ad libitum sampling methods, as well as faecal (n=54) and anogenital scent (n=35) samples of the breeding female. We measured sex hormone levels using enzyme immunoassay technique and investigated the volatile component of odour signals using solid-phase microextraction and gas chromatography-mass spectrometry. We observed sexual and aggressive behaviours occasionally during the breeding period. Our regression analysis showed that only period significantly predicted rates of female anogenital scent-marking, whereby the female performed anogenital scent-marking more frequently during the breeding rather than the non-breeding period. In contrast, female hormone levels did not significantly explain variation in rates of neither male nor female olfactory, sexual and affiliative behaviours, suggesting that individuals’ behaviour alone is not an effective indicator of the ovulation window. The volatile chemical profile of anogenital odour secretions changed over the study, with four compounds distinguishing the fertile window during the breeding period. In conclusion, our findings suggest that anogenital scent-marking may signal the reproductive status of captive female gentle lemurs.